2023
DOI: 10.3390/su15042996
|View full text |Cite
|
Sign up to set email alerts
|

Determining Factors Affecting Perceived Customer Satisfaction on Public Utility Bus System in Occidental Mindoro, Philippines: A Case Study on Service Quality Assessment during Major Disruptions

Abstract: The imposition of lockdown due to the COVID-19 pandemic has affected the majority of enterprises throughout the globe. The public transportation sector was greatly affected, especially in provincial areas in the Philippines. This study aimed to investigate the service quality of bus transits in Occidental Mindoro during the COVID-19 pandemic using Analytical Hierarchy Process (AHP) and SERVQUAL dimensions. A total of 200 individuals completed a 67-question online questionnaire. AHP was utilized to determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…In fact, it is unsurprising that users of e-hailing taxi services accord significance to safety as a service quality measure. This will arise from the safety concern of the users since public transportation has a higher safety risk because it usually carries more than one non-related person in a car [51]. In line with this study, [52] applied AHP to service quality factors and found that safety has the most significant weight for bus services in the Philippines.…”
Section: Discussion Of Resultsmentioning
confidence: 61%
“…In fact, it is unsurprising that users of e-hailing taxi services accord significance to safety as a service quality measure. This will arise from the safety concern of the users since public transportation has a higher safety risk because it usually carries more than one non-related person in a car [51]. In line with this study, [52] applied AHP to service quality factors and found that safety has the most significant weight for bus services in the Philippines.…”
Section: Discussion Of Resultsmentioning
confidence: 61%
“…Hence, this study supposes that the assurance dimension will affect the passengers' satisfaction with MRT. Accordingly, the hypothesis here is-between customer satisfaction and the empathy construct of service quality (Ananda et al, 2023;Putta, 2023;Jou et al, 2023). Thus, the authors daresay that the empathy dimension will affect the passengers' satisfaction with MRT.…”
Section: Evaluating the Satisfaction Of Passengers Towards Metro Rail...mentioning
confidence: 93%
“…Furthermore, in several attempts to apply SERVQUAL or SERV-PERF to the public service context, the need for adaptation and creation of items is clearly observed (Akdere et al, 2020;Butkus et al, 2023;Dung, 2021;Jou et al, 2023;Maagi & Mwakalobo, 2023;Moura e Sá et al, 2021;Sharma & Al Sinawi, 2021;Sohail & Hasan, 2021). Some examples among the various proposed indicators are those related to transparency (Lim & Lee, 2021;López-Lemus, 2023;Tanny & Zafarullah, 2023;Witesman et al, 2022), doing the right thing for the country (Ali AlShehail et al, 2022;Bucaite Vilke & Vilkas, 2018;Chien & Thanh, 2022;López-Lemus, 2023;Tanny & Zafarullah, 2023), and civil servants' ethics and capacity (Chien & Thanh, 2022;López-Lemus, 2023;Tanny & Zafarullah, 2023).…”
Section: Reasons To Create a New Scalementioning
confidence: 99%
“…Tangible aspects represent the first dimension, which was structured with nine items, whose aim is to identify the user's perception of the physical characteristics of the public body. In this sense, several studies use the tangible aspects dimension to evaluate physical facilities, equipment, general appearance, accommodations, communication, and information technologies, among others (Jou et al, 2023;Luyen & Thanh, 2022;Maagi & Mwakalobo, 2023;Riani, 2023;Sulemana et al, 2023). For Jou et al (2023), tangible aspects contribute to the perception of the experience in an efficient, empowered, and positive way, being highly significant for the quality of the service.…”
Section: Construction Of Publicservmentioning
confidence: 99%
See 1 more Smart Citation